Factors that influence banking performance: a narrative literature review - Asmana, Yandi; Tukiran, Martinus; Sukardi, Sukardi; Zainuddin, Zulkifli (UJoST- Universal Journal of Science and Technology, 2024)
The research findings consistently indicate that the emergence of alternative digital credit, provided by FinTech and BigTech firms, has a significant and negative impact on the performance of the banking sector. This impact is observed in both developed and developing countries, leading to decreased bank returns, intermediation margins, and profitability. The negative effect is influenced by various factors, including the degree of stability and market power in the banking sector, the level of competition, and the extent of physical banking infrastructure. Additionally, the growth of digital lending is negatively correlated with banking credit, suggesting a potential substitution effect. The studies address endogeneity concerns and conduct robustness tests to confirm the findings, ensuring the reliability of the results. The implications of the research suggest that the banking industry may need to adapt its business models to compete in an increasingly digital environment, and policymakers should consider regulating new participants in the credit markets to ensure financial stability. These findings provide valuable insights into the impact of alternative digital credit on the banking industry's performance, highlighting the need for banks to adapt to the changing landscape of digital finance and the potential implications for financial stability.